The Influence of Inflation Rates on International Tourist Arrivals via Air Gateways in Indonesia During 2017-2024 (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to analyze the effect of the inflation rate on the number of Wismanto Indonesia Via Air Gateway. The data used covers the period from January 2017 to September 2024, focusing on the relationship between inflation as a macroeconomic factor and the number of tourists visiting Indonesia. The data analysis used in this study is regression analysis, supported by descriptive analysis of each variable. The regression analysis results show that the inflation rate has a significant positive effect on the number of international tourist arrivals. The regression coefficient of 156,266 indicates that every 1% increase in inflation has the potential to increase the number of international tourists by 156,266 individuals. The significance value of 0.000 indicates that this relationship is statistically significant at the 95% confidence level. These findings provide an understanding that although inflation is often associated with rising prices of goods and services, in the context of Indonesian tourism, inflation can be linked to other factors, such as exchange rate fluctuations, which increase Indonesia's appeal as a tourist destination. This study recommends that the government and stakeholders in the tourism sector consider the impact of inflation in tourism development strategies, while maintaining economic stability and international competitiveness. Further studies are recommended to explore other mediating variables, such as exchange rates and tourism promotion policies, in order to understand this relationship more comprehensively.